An empirical Study on Emotional Intelligence and Cognitive Ability towards Online Learning among Youngsters for equipping future Workforce - Dara Vijaya Lakshmi (Journal of Informatics Education and Research, 2024)
Emotional intelligence involves an ability to carry out accurate reasoning about emotions and ability to apply emotions, emotional cognizance to enhance thought. Emotional intelligence facilitates to foresee success since it reflects how a person applies knowledge to his/her immediate situation. Emotional intelligence measures common sense and ability to get conversant professional among humankind. EI leads capacity to build positive outcomes through relationships with others and to one-self. The pivotal aspect in this review is that it addresses the relation between EI measures and meaningful criteria including social and environmental outcomes, performance, psychological and physical well-being. Emotional connectivity with e-learning especially during Covid-19 becomes key aspect of effective learning and development. E-Learning design and development is not a new idea. The current research was conducted among young students pursuing under graduation to explore the impact of emotional intelligence in eLearning how their emotional facilitation of thinking improves their engagement. Human brain is not just a cognitive information processing mechanism, but a complicated system where affective and cognitive functions are inseparably integrated. Present study primarily revolves around emotional training, maturing, and development. The discussion section is followed with list of crucial aspects and recommended measures for future research prospects the practical implications of emotional intelligence.